CO2 Enrichment in Anode Loop and Correlation with CO Poisoning of Low Pt Anodes in PEM Fuel Cells1. Issue 5 (26th July 2018) - Erbach, S.; Epple, S.; Heinen, M.; Toth, G.; Klages, M.; Gaudreau, D.; Ages, M.; Putz, A.
Abstract: In automotive fuel cell systems anode fuel re‐circulation is often used to achieve high hydrogen utilization rates which reduces the hydrogen consumption of the fuel cell car, as well as it is an appropriate way to control hydrogen emissions. During operation hydrogen is consumed, while residual gases increase in the previously mentioned hydrogen loop. Besides nitrogen, we have found that CO2 accumulates in the anode loop and concentrations between 150–350 ppm were measured for varying current densities. We attribute this finding to CO2 crossover from the cathode to the anode and subsequent enrichment in the anode loop. To study the effect of this relatively small CO2 ‐concentration on the cell performance, tests were conducted with a proton exchange membrane (PEM) 45 cm 2 single test cell with contaminated hydrogen/air feed. The data clearly indicate that electrochemical reduction of CO2 to CO takes place which has a significant impact on the cell performance due to blocked catalyst sites by CO affecting the current density of the hydrogen oxidation reaction (HOR). The measurements with hydrogen containing CO2 were matched with hydrogen plus CO measurements to quantify the impact and to determine a "CO‐equivalent concentration" for CO2 . Consequences for the operation strategy of fuel cell systems are given.